DETERMINAN MINAT MELANJUTKAN PENDIDIKAN KE PERGURUAN TINGGI SISWA KELAS XII IPS SMA NEGERI 1 WIROSARI KABUPATEN GROBOGAN TAHUN AJARAN 2017/2018 - Putri, Dessy Anggara Listy; Kusmuriyanto, Kusmuriyanto (Economic Education Analysis Journal, 2017)
The purpose of this research is to determine the influence of the family environment, school environment, peers environment, and self efficacy on interest in continuing education to college directly and indirectly. The population of the research are student of 12th IPS at SMA Negeri 1 Wirosari academic year 2017/2018 that amount 99 students. The methods of data collecOktober questionnaire. The methods of analysis was partial test and sobel test to determine the relationship between variable was done. The result of this study show that family environment, school environment, peers environment, and self efficacy has positive and significant to interest in continuing education to college. Self efficacy can mediate the effect of family environment and school environment to interest in continuing education to college, while the effect of peers environment on interest in continuing education to college can not be mediated through self efficacy.